TGF-beta1 regulates human brain pericyte inflammatory processes involved in neurovasculature function. Issue 1 (December 2016) - Rustenhoven, Justin; Aalderink, Miranda; Scotter, Emma; Oldfield, Robyn; Bergin, Peter; Mee, Edward; Graham, E.; Faull, Richard; Curtis, Maurice; Park, Thomas; Dragunow, Mike
Abstract Background Transforming growth factor beta 1 (TGFβ1 ) is strongly induced following brain injury and polarises microglia to an anti-inflammatory phenotype. Augmentation of TGFβ1 responses may therefore be beneficial in preventing inflammation in neurological disorders including stroke and neurodegenerative diseases. However, several other cell types display immunogenic potential and identifying the effect of TGFβ1 on these cells is required to more fully understand its effects on brain inflammation. Pericytes are multifunctional cells which ensheath the brain vasculature and have garnered recent attention with respect to their immunomodulatory potential. Here, we sought to investigate the inflammatory phenotype adopted by TGFβ1 -stimulated human brain pericytes. Methods Microarray analysis was performed to examine transcriptome-wide changes in TGFβ1 -stimulated pericytes, and results were validated by qRT-PCR and cytometric bead arrays. Flow cytometry, immunocytochemistry and LDH/Alamar Blue® viability assays were utilised to examine phagocytic capacity of human brain pericytes, transcription factor modulation and pericyte health. Results TGFβ1 treatment of primary human brain pericytes induced the expression of several inflammatory-related genes (NOX4, COX2, IL6 andMMP2 ) and attenuated others (IL8, CX3CL1, MCP1 andVCAM1 ). A synergistic induction of IL-6 was seen with IL-1β/TGFβ1 treatment whilst TGFβ1 attenuated the IL-1β-induced expression of CX3CL1, MCP-1 and sVCAM-1. TGFβ1 was found to signal through SMAD2/3 transcription factors but did not modify nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) translocation. Furthermore, TGFβ1 attenuated the phagocytic ability of pericytes, possibly through downregulation of the scavenger receptors CD36, CD47 and CD68. Whilst TGFβ did decrease pericyte number, this was due to a reduction in proliferation, not apoptotic death or compromised cell viability. Conclusions TGFβ1 attenuated pericyte expression of key chemokines and adhesion molecules involved in CNS leukocyte trafficking and the modulation of microglial function, as well as reduced the phagocytic ability of pericytes. However, TGFβ1 also enhanced the expression of classical pro-inflammatory cytokines and enzymes which can disrupt BBB functioning, suggesting that pericytes adopt a phenotype which is neither solely pro- nor anti-inflammatory. Whilst the effects of pericyte modulation by TGFβ1 in vivo are difficult to infer, the reduction in pericyte proliferation together with the elevated IL-6, MMP-2 and NOX4 and reduced phagocytosis suggests a detrimental action of TGFβ1 on neurovasculature.